Biochemical Components Associated With Microbial Community Shift During the Pile-Fermentation of Primary Dark Tea - Li, Qin; Chai, Shuo; Li, Yongdi; Huang, Jianan; Luo, Yu; Xiao, Lizheng; Liu, Zhonghua (Frontiers in Microbiology, 2018)
Primary dark tea is used as raw material for compressed dark tea, such as Fu brick tea, Hei brick tea, Hua brick tea and Qianliang tea. Pile-fermentation is the key process for the formation of the characteristic properties of primary dark tea, during which microorganism play an important role. In this study, the changes of major chemical compounds, enzyme activities, microbial diversity and their correlations were explored during the pile-fermentation process. Our chemical and enzymatic analysis showed that the contents of the major compounds were decreased, while the activities of polyphenol oxidase, cellulase and pectinase were increased during this process, except peroxidase activity that could not be generated from microbial communities in primary dark tea. The genera Cyberlindnera, Aspergillus, Uwebraunia, Unclassified Pleosphorales of fungus and Klebsiella, Lactobacillus of bacteria were predominant in the early stage of the process, but only Cyberlindnera and Klebsiella were still dominated in the late stage and maintained a relatively constant until the end of the process. The amino acid was identified as the important abiotic factor in shaping the microbial community structure of primary dark tea ecosystem. Network analysis revealed that the microbial taxa were grouped into five modules and seven keystone taxa were identified. Most of the dominant genera were mainly distributed into module Ⅲ, it indicated that this module was important for the pile-fermentation process of primary dark tea. In addition, O2PLS analysis revealed that the fungi made more contributions to the formation of the characteristic properties of primary dark tea than bacteria during the pile-fermentation process. Furthermore, ten microbial genera including Cyberlindnera, Aspergillus, Eurotium, Uwebraunia, Debaryomyces, Lophiostoma, Peltaster and Klebsiella, Aurantimonas, Methylobacterium were identified as core functional genera for the pile-fermentation of primary dark tea. This study provides useful information for improving our understanding on the formation mechanism of the characteristic properties of primary dark tea during the pile-fermentation process.